2001
DOI: 10.1159/000049190
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin GM and KM Allotypes in Systemic Lupus erythematosus

Abstract: Genetic variation in immunoglobulin γ (GM) and ĸ (KM) chains was associated with systemic lupus erythematosus (SLE) in some studies. However, the data are conflicting, and only one study examined associations in African-Americans. We examined GM and KM allotypes, by race, in a population-based case-control study of SLE. Sera from patients (n = 222) and controls (n = 273) were typed for GM and KM allotypes by a hemagglutination inhibition method. GM phenotypes were not significantly associated with SLE in Afric… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The most simple explanation is the established association between the homozygous presence of G2M(n) and the findings of quantitatively strong Ab responses to polysaccharide Ags (18,19). Several mechanisms have been suggested through which G2M*n and the associated GM*b;f;n haplotype might promote Ab responses, including involvement of haplotype-linked genes and slow processing of Ag by macrophages (17,18,52). Circulating CD27…”
Section: Discussionmentioning
confidence: 99%
“…The most simple explanation is the established association between the homozygous presence of G2M(n) and the findings of quantitatively strong Ab responses to polysaccharide Ags (18,19). Several mechanisms have been suggested through which G2M*n and the associated GM*b;f;n haplotype might promote Ab responses, including involvement of haplotype-linked genes and slow processing of Ag by macrophages (17,18,52). Circulating CD27…”
Section: Discussionmentioning
confidence: 99%
“…Of particular relevance here, GM and KM allotypes influence immune responsiveness to certain autoantigens [22,42], and KIR-MHC class I interactions modify the NK cell cytotoxic activity and NK cell cytokine production profile [43]. Evidence for epistatic contributions of unlinked genes to the risk of autoimmune diseases is accumulating rapidly [44].…”
Section: Discussionmentioning
confidence: 99%
“…Using hypothesis driven candidate gene approaches, numerous studies have identified particular GM genes as risk factors for many malignant [9-13], infectious [14-18], and autoimmune diseases [19-24], but most of these findings have not been confirmed or refuted by modern genome-wide association studies (GWAS). One contributing factor might be the absence of GM gene probes in most genotyping platforms.…”
Section: Gm Allotypes and Disease Susceptibilitymentioning
confidence: 99%